A study on factors of job turnover intentions among staff at PUTRA Specialist Hospital Malacca / Asilah Alwani Kasim and Siti Norhazwani Hamzah - Kasim, Asilah Alwani; Hamzah, Siti Norhazwani (Faculty of Business Management, 2016)
PUTRA Specialist Hospital is one of private hospital that located nearest town of Malacca. Even though PUTRA Specialist Hospital has more than 600 members in the company but there were still occurred turnover even not in critical phase. Therefore, PUTRA Specialist Hospital should aware have the factors of retention in order to attract and retain their employees in the organization. In this research, the aim is to study the factors that might lead to job turnover intention that happens in almost every organization sector and organization struggling to manage this issue in order to maintain their company’s performance. This study involves three major factors lead to job turnover intentions which are job stressor, working environment and also work overloads. For the analysis of the study a total of 234 employees will be chosen from different department at PUTRA Specialist Hospital. In order to indicate the result, five type of data analysis will be used and conduct for this research which are Reliability Analysis, Frequency Analysis, Descriptive Statistic Analysis, Pearson Correlation Analysis and Multiple Regression Analysis. Reliability Analysis is been conducted to test he reliability of the questions in questionnaire whether is acceptable or problematic. Frequency Analysis been used to analyze demographic data which is on Section A in questionnaire. Meanwhile, Descriptive Statistics Analysis to look on the mean, mode and median of the questions comprised in questionnaire. Pearson Correlation Analysis is to analyze the relationship between variables and follows rules of thumb of correlation coefficient size. In Multiple Regression Analysis, researcher will look on significant relationship between variables the most influential towards dependent variable. Researcher also gives some recommendation based on the result of findings in order to improve for future research. Overall, organization should create attractive environment to help their employees to work more efficient and turnover intention can be reduce.